Decoupling the functional roles of cationic and hydrophobic groups in the antimicrobial and hemolytic activities of methacrylate random copolymers - Mortazavian, Hamid (Biomacromolecules, 2018)
In this study, we report that the antimicrobial and hemolytic activities of ternary statistical methacrylate copolymers consisting of cationic ammonium (amino-ethyl methacrylate: AEMA), hydrophobic alkyl (ethyl methacrylate: EMA), and neutral hydroxyl (hydroxyethyl methacrylate: HEMA) side chain monomers. The cationic and hydrophobic functionalities of copolymers mimic the cationic amphiphilicity of naturally occurring antimicrobial peptides (AMPs). The HEMA monomer units were used to separately modulate the compositions of cationic and hydrophobic monomers, and we investigated the effect of each component on the antimicrobial and hemolytic activities of copolymers. Our data indicated increasing the number of cationic groups of copolymers to be more than the 30 mole % did not increase their antimicrobial activity against Escherichia coli. The number of cationic side chains in a polymer chain at this threshold is 5.5 −7.7, which is comparable to those of natural antimicrobial peptides such as maginin (+6). On the other hand, the MIC values of copolymers with > 30 mole % of AEMA depend on only the mole % of EMA, indicating that the hydrophobic interactions of copolymers with E. coli cell membranes determine the antimicrobial activity of copolymers. These results suggest that the roles of cationic and hydrophobic groups can be controlled independently by design in the ternary copolymers studied here.